Antibiotic prescribing and resistance: knowledge level of medical students of clinical years of University Sultan Zainal Abidin, Malaysia - Haque M; Rahman NIA; Zulkifli Z; Ismail S (Dove Medical Press, 2016)
Mainul Haque, Nor Iza A Rahman, Zainal Zulkifli, Salwani Ismail Faculty of Medicine, Universiti Sultan Zainal Abidin, Kuala Terengganu, Terengganu, Malaysia Abstract: The innovation of penicillin by Dr Alexander Fleming in 1928 and its use in clinical practice saved many lives, especially during the Second World War. Tuberculosis still carries a significant public health threat and has re-emerged over the past two decades, even in modern countries where tuberculosis was thought to be eliminated. The World Health Organization defines antimicrobial resistance as the resistance of a microorganism to an antimicrobial drug that was initially effective for treatment of infections caused by the microbe. Therefore, the findings of the current study will provide data to enable the design of a new educational program to better equip our students in confronting antimicrobial resistance. This study was a cross-sectional, questionnaire-based survey, which was undertaken in the Faculty of Medicine, Universiti Sultan Zainal Abidin, Kuala Terengganu, Malaysia. The study participants were students of the Bachelor of Medicine and Bachelor of Surgery program (MBBS) of Year III, IV, and V. A total of 142 out of 164 (86%) medical students returned the questionnaire. Specifically, the year-wise breakdown of responses was 29% (41), 39% (55), and 32% (45) for Year III, IV, and V, respectively. Among the study respondents, 28% (40) were male, and the remaining 72% (102) were female. In all, 67% of the participants felt more confident in “making an accurate diagnosis of infection/sepsis.” The majority (88%) of the study participants stated that they would like more training on antibiotic selection. This research has found that there is a gap between theoretical input and clinical practice; the students are demanding more educational intervention to face the threat of antimicrobial resistance. Keywords: antibiotic, prescribing, resistance, medical students, knowledge, Malaysia